Silver nanoparticle synthesis using pineapple waste: article - Syed Omar, Syed Muhammad Zulfazli; Abd. Hashib, Syafiza (2017)
Nanoparticles is one of the new technology in this century. This technology help human being to control the behavior of material at molecular level. There are three method to produce nanoparticles which are physical method, chemical method and biological method. Biological method is more preferred from other two methods because it is eco-friendly, safer and low operation cost. Usually, plant parts or microorganism is used as raw material in biological synthesis. However, plant part is preferred to use because it is easy to handle than microorganism. A waste from plant part is suggested instead of fresh part because it can reduce the operation cost and reduce the waste produced. Abundant of pineapple waste is an example of plant part that has potential in biological method. Waste from pineapple which is peel was studies in potential of nanoparticle material. This study was underwent four simple step which are extraction process, synthesis process, purification stage and analyzing stage. Firstly, pineapple peel was extracted to get the biomolecule. The peel extract solution was analyzed using FTIR. Analysis from FTIR was verified the peel has biomolecule such as protein, Bromelain and Vitamin C. So, peel extract was used as reduction and capping agent to prepare Silver Nanoparticles, the process is called biological method. Then, it is added into AgNO3 solution and the mixture was stirred. The colorless of AgNO3 solution was changed to the dark brown solution after peel extract was added. After that, the dark brown solution or called as AgNPs was analyzed by UV-vis instrument. The absorbance peak of UV-vis spectrum in range of 400 nm to 500 nm shows there is AgNPs in that solution. Then, the solution was analyzed by FTIR to verify the changing of functional group. AgNPs solution was dried to get the power form. Then, it was further characterized by using FESEM. The size of AgNPs was formed in range from 20 nm to 30 nm. The peel extract has potential in the synthesis of nanoparticles and the formation of nanoparticles can be controlled by manipulating the volume ratio, stirring time and AgNO3 solution concentration.